An in-depth look into the association between morningness–eveningness and well-being: evidence for mediating and moderating effects of personality. (2nd January 2019) - Drezno, Magdalena; Stolarski, Maciej; Matthews, Gerald
ABSTRACT: Morningness–eveningness and standard personality traits are associated with well-being but few studies have directly compared the two types of construct as correlates of life satisfaction. Influences on well-being common to both chronotype and personality may include shared biological bases for depression and sleep disturbance, tendencies toward social jetlag, and emotion-regulation mechanisms. The current study tested mediation and moderation hypotheses in a sample of 379 Polish adults. The first hypothesis was that conscientiousness and emotional stability traits would mediate the relationship between morningness and life satisfaction. Consistent with previous results, morningness, the two personality traits, and satisfaction tended to be mutually positively correlated. A multiple mediation analysis showed that both traits partially mediated the morningness–satisfaction association. Data are compatible with morningness influencing personality development adaptively, although other causal hypotheses could be advanced. The second hypothesis was that extraversion would moderate the association between chronotype and satisfaction. This hypothesis was supported, with extraverted evening types showing disproportionately high life satisfaction, whereas introverted evening types showed the lowest levels of satisfaction. Level of extraversion may influence whether or not evening types choose to engage in adaptive social activities that boost well-being during the evening hours. Results demonstrate the importance of investigating both chronotype and personality in studies of well-being.